Investigating the Effect of Perception of Air Pollution, the Level of Noise Perception with Quality of Life and the Possibility of Mental Disorders with the Moderating Role of Psychological Hardiness in Residents of Areas Close to Industrial City (Tehran) - Ahmadi, Mona; Sadeghi, Parnia; Norouzi Khotbesarah, Saeed; javanmard, Ebrahim; Mahdieh Arani, Zakieh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The purpose of this study is to explore how people’s perceptions of air and noise pollution impact their quality of life. It also aims to examine the potential for mental disorders, with a focus on the moderating influence of psychological hardiness, among individuals living near industrial sites in Tehran. Methods and Materials: The current study was a part of descriptive-correlational research and utilized a cross-sectional research method. The researchers employed a structural model and path analysis to examine the impact of the moderating variable. The statistical population for this study consisted of all individuals residing in proximity to industrial areas (industrial towns) in Tehran from July to October 2023. A sample of 152 participants was randomly chosen using a multi-stage cluster sampling technique. The research instruments utilized in the study were Kobasa’s Hardiness Scale (KHS), World Health Organization Quality-of-Life Scale (WHOQOL-BREF), Symptom Checklist-90 (SCL90), Air Pollution Perception Survey, and Noise Exposure Questionnaire (NEQ). Descriptive statistics and the moderating variable’s effects were analyzed using JAMOVI version 2.4 software, while Smart PLS version 4 software was used to assess the relationships between variables. A p-value of 0.05 was deemed appropriate in this study. Findings: The current study’s findings indicate that the variable of Hardiness played a moderating role in the connection between the level of Noise perception and Phobic anxiety, with a notable impact observed (β=0.139, P=0.031). Furthermore, Hardiness was also found to moderate the relationship between the level of Noise perception and Obsessive-compulsive disorder, with a significant effect noted (β=0.155, P=0.026). In addition, the study revealed that Hardiness moderated the association between air pollution perception and Obsessive-compulsive disorder, with a significant effect evident (β=0.485, p<0.001). Moreover, the results showed that Hardiness moderated the relationship between air pollution perception and quality of life, with a significant effect observed (β=0.267, p<0.001). Conclusion: The findings of this study demonstrated that both air and noise pollution have the potential to increase mental disorders and decrease the quality of life. However, developing psychological hardiness can help mitigate these adverse consequences. These findings have valuable implications for people living in industrial zones, employees exposed to high levels of pollution, and authorities in charge of public health.